2020
DOI: 10.1161/circresaha.119.315506
|View full text |Cite
|
Sign up to set email alerts
|

Enriched Marine Oil Supplements Increase Peripheral Blood Specialized Pro-Resolving Mediators Concentrations and Reprogram Host Immune Responses

Abstract: Rationale: Specialized pro-resolving mediators (SPM—lipoxins, resolvins, protectins, and maresins) are produced via the enzymatic conversion of essential fatty acids, including the omega-3 fatty acids docosahexaenoic acid and n-3 docosapentaenoic acid. These mediators exert potent leukocyte directed actions and control vascular inflammation. Supplementation of animals and humans with essential fatty acids, in particular omega-3 fatty acids, exerts protective actions reducing vascular and systemic i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
79
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 110 publications
(83 citation statements)
references
References 35 publications
4
79
0
Order By: Relevance
“…EPA driving an upregulation in the concentration of RvE1's precursor is highly consistent with a recent clinical trial to show that consumption of an n-3 PUFA supplement promoted a strong upregulation of SPMs within 24 hours. 44 A major advancement is that our data show RvE1 could improve hyperinsulinemia and hyperglycemia via ERV1/ ChemR23. RvE1 treatment is likely exerting its effects through multiple mechanisms.…”
Section: F I G U R Ementioning
confidence: 76%
“…EPA driving an upregulation in the concentration of RvE1's precursor is highly consistent with a recent clinical trial to show that consumption of an n-3 PUFA supplement promoted a strong upregulation of SPMs within 24 hours. 44 A major advancement is that our data show RvE1 could improve hyperinsulinemia and hyperglycemia via ERV1/ ChemR23. RvE1 treatment is likely exerting its effects through multiple mechanisms.…”
Section: F I G U R Ementioning
confidence: 76%
“…It is important to note that over-the-counter formulations of these fatty acids are not the same as prescriptions due to differences in dose, purity, and composition of the fatty acids. Nevertheless, a recent study showed that an SPM precursor containing marine oil strongly upregulated SPMs of the EPA and DHA series within hours of administration accompanied by enhanced neutrophil and monocyte phagocytosis of bacteria (62). However, a major limitation of this approach is that dietary EPA and DHA may not be as potent as direct intervention with SPMs (12).…”
Section: Discussionmentioning
confidence: 99%
“…Another interesting focus area for a potential follow-up study could be the specialized ­pro-resolving mediators (SPM-lipoxins, resolvins, protectins, and maresins) that are produced by enzymatic conversion of essential FAs, including omega-3 PUFAs. Inasmuch, DHA- and EPA-derived SPMs may help in the reduction of vascular and systemic inflammation [ 28 ]. Hence, increasing dietary omega-3 intake may have wide health benefits that are not limited to omega-3 PUFAs directly [ 1 ].…”
Section: Discussionmentioning
confidence: 99%